PENGARUH SUSTAINABILITY REPORT DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Vira Oktaviani Putri; Primadonna Ratna Mutumanikam (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2022)
The research aims to analyze the effect of sustainability report and firm size on firm value with profitability as moderation variable in infrastructure, utility, and transportation companies in Indonesian Stock Exchange period 2016-2018. This research use quantitative method. The population in this research are infrastructure, utility, and transportation companies in Indonesian Stock Exchange period 2016-2018. The sample selection use purpose sampling method, sample obtained as many 10 companies. The data analyze technique use for this research is multiple regression analysis which is include normality test, classical assumption test and hypothesis test. The result of research show that sustainability report has no significant effect on firm value, firm size has a significant negative effect on firm value, profitability weaken the effect of sustainability report on firm value and profitability strengthen the effects of firm size on firm value.